Prototype Portable Electrical Resistance Tomography - Ahmad Zaenal Hayat; Agung Tjahjo Nugroho; Nurul Priyantari (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Tomography is a way to describe something non-destructively. Some types of Tomography are Electrical Resistance Tomography (ERT), Electrical Impedance Tomography (EIT), and Electrical Capacitance Tomography (ECT). This study aims to combine the ECT and ERT systems. The combination uses the ERT technique (Borehole method) and develops until it can be used like ECT. This research conducts three significant stages (design making, designed realization, and examination). The examination is carried out by simulation and experimental measurement. The simulation result is compared to the result of the experimental measurement. The result shows that both have the same patterns, but it has the amplitude of voltage difference pattern. It is because the resistivity result affects the measured voltage difference result. The higher the resistivity result of the medium, the smaller the measured voltage difference.Tomography is a way to describe something non-destructively. Some types of Tomography are Electrical Resistance Tomography (ERT), Electrical Impedance Tomography (EIT), and Electrical Capacitance Tomography (ECT). This study aims to combine the ECT and ERT systems. The combination uses the ERT technique (Borehole method) and develops until it can be used like ECT. This research conducts three significant stages (design making, designed realization, and examination). The examination is carried out by simulation and experimental measurement. The simulation result is compared to the result of the experimental measurement. The result shows that both have the same patterns, but it has the amplitude of voltage difference pattern. It is because the resistivity result affects the measured voltage difference result. The higher the resistivity result of the medium, the smaller the measured voltage difference.